Antimicrobial Resistance as a Hidden Menace Lurking Behind the COVID-19 Outbreak: The Global Impacts of Too Much Hygiene on AMR - Rezasoltani, Sama; Yadegar, Abbas; Hatami, Behzad; Asadzadeh Aghdaei, Hamid; Zali, Mohammad Reza (Frontiers in Microbiology, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new coronavirus that was recently discovered in 2019. While the world is working hard to overcome and control the COVID-19 pandemic, it is also crucial to be prepared for the great impacts of this outbreak on the development of antimicrobial resistance (AMR). It is predicted that, inappropriate and too much use of antibiotics, biocides and disinfectants during this pandemic may raise disastrous effects on antibiotic stewardship programmes and AMR control all around the world. Furthermore, the use of certain antibiotics alone or in combination with antiviral agents or other medications for the treatment of secondary bacterial infections among COVID-19 patients, may be a regarded as major factor that negatively affects host immune response by disrupting mitochondrial function and activity. Herein, we suggest that the current management strategies to control AMR and prioritize antibiotic stewardship schemes should be extremely highlighted in relation to COVID-19 outbreak. The rising concerns about excessive use of antimicrobials and biocides and taking too much hygiene also need to be addressed during this pandemic due to their impacts on AMR, public health and environment.